Magnetic resin composition, and electronic component
The magnetic resin composition, featuring an iron alloy filler with specific particle sizes coated with silicon oxides, addresses the challenges of achieving high flowability, permeability, and insulation by maintaining these properties in the cured product, thus enhancing the performance of electronic components.
Patent Information
- Application Number
- JP2023166541
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-09
AI Technical Summary
Existing magnetic resin compositions face challenges in achieving high flowability, permeability, and insulation properties simultaneously, particularly when increasing the filling rate of soft magnetic metal fillers, which often leads to decreased electrical insulation and increased eddy current losses.
A magnetic resin composition comprising an iron alloy filler with specific particle size ranges (10 μm to 50 μm and 1 μm to 5 μm) coated with silicon oxides, combined with a thermosetting resin and a curing agent, which maintains good flowability and enhances the magnetic permeability and insulation properties of the cured product.
The proposed magnetic resin composition achieves high flowability, leading to excellent moldability, while the cured product exhibits high magnetic permeability and insulation properties, reducing eddy current losses and maintaining voltage resistance.
Smart Images

Figure 2025056971000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a magnetic resin composition and an electronic component, and more particularly to a magnetic resin composition containing iron alloy particles, and an electronic component including a cured product of this magnetic resin composition. [Background technology]
[0002] Patent Document 1 discloses the use of a magnetic molding resin that covers the surface of a substrate so as to embed electronic components in an electronic circuit package, and describes that the magnetic molding resin contains a filler, which is a magnetic filler that is 61 to 68% by weight Fe, 32 to 39% by weight Ni or Ni substituted with 8% or less by weight Co, and a non-magnetic filler. It also describes that the magnetic molding resin can be mainly composed of a thermosetting material, and that the surface of the magnetic filler can be coated with an insulating coating. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-135770 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present disclosure is to provide a magnetic resin composition which can be made highly fluid and which, when cured, has high magnetic permeability and high insulating properties, and an electronic component. [Means for solving the problem]
[0005] A magnetic resin composition according to one embodiment of the present disclosure contains an iron alloy filler (A), a thermosetting resin (B), and a curing agent (C). The iron alloy filler (A) contains a first filler (a1) and a second filler (a2). The first filler (a1) comprises iron alloy particles containing all of iron, silicon, boron, and carbon atoms, and a silicon oxide coating the surface of the iron alloy particles, and has an average particle size of 10 μm to 50 μm. The second filler (a2) comprises iron alloy particles containing all of iron, silicon, boron, and carbon atoms, and a silicon oxide coating the surface of the iron alloy particles, and has an average particle size of 1 μm to 5 μm.
[0006] According to an aspect of the present disclosure, there is provided an electronic component including a passive element and a sealing portion that seals the passive element, the sealing portion including a cured product of the magnetic resin composition. Effect of the Invention
[0007] According to the present disclosure, a magnetic resin composition and electronic component can be obtained that can have high fluidity and achieve high magnetic permeability and high insulating properties after curing. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic perspective view illustrating an example of an electronic component according to an embodiment. [Diagram 2] Fig. 2A is a schematic cross-sectional view showing an example for producing an electronic component according to an embodiment, and Fig. 2B is a schematic cross-sectional view showing an example of a state in which a cavity of the electronic component according to an embodiment is sealed. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing an example of an electronic component covered with the magnetic resin composition according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] 1. Overview Hereinafter, one embodiment of the present disclosure will be described. Note that the following embodiment is merely one of various embodiments of the present disclosure. The following embodiment can be modified in various ways depending on the design as long as the object of the present disclosure can be achieved.
[0010] Conventionally, in electronic components having an inductor, a resin material containing a resin component is used to cover or seal the inductor. In order to reduce the size of electronic components and electronic devices having electronic components, and to increase the inductance of the inductor, a magnetic resin composition containing a soft magnetic metal component in a resin material has been used. When a sealing part that covers or seals an inductor is made from a cured product of a magnetic resin composition, the magnetic permeability of the sealing part is increased, and the size of the sealing part, such as the thickness, can be reduced, thereby realizing the miniaturization of electronic components and electronic devices. In addition, by increasing the magnetic permeability of the sealing part, the inductance of the inductor can be increased. This can improve the performance of an electronic device composed of electronic components, and for example, when the electronic device is a converter, the converter can achieve high conversion efficiency.
[0011] In order to increase the magnetic permeability of the cured product, it is necessary to increase the filling rate of the soft magnetic metal filler in the magnetic resin composition. However, according to the inventors' investigation, as the filling rate of the soft magnetic metal filler increases, the electrical insulation of the cured product decreases. In addition, the fluidity of the magnetic resin composition decreases. Furthermore, when the particles of the soft magnetic metal filler come into contact with each other in the hardened material, eddy currents are generated between the particles, which increases the eddy current loss.
[0012] Therefore, in order to solve the above problems, the inventors conducted intensive research and discovered the magnetic resin composition of the present disclosure, which can maintain good fluidity, increase the magnetic permeability of the cured product, and achieve good insulation properties.
[0013] The magnetic resin composition according to the present embodiment contains an iron alloy filler (A), a thermosetting resin (B), and a curing agent (C). The iron alloy filler (A) contains a first filler (a1) and a second filler (a2). The first filler (a1) comprises iron alloy particles containing all of the atoms of iron, silicon, boron, and carbon, and a silicon oxide coating the surface of the iron alloy particles, and has an average particle diameter of 10 μm to 50 μm. The second filler (a2) comprises iron alloy particles containing all of the atoms of iron, silicon, boron, and carbon, and a silicon oxide coating the surface of the iron alloy particles, and has an average particle diameter of 1 μm to 5 μm. The reason why the magnetic resin composition according to the present embodiment can maintain good fluidity, and the cured product thereof has high magnetic permeability and good insulating properties has not been clarified, but is presumed to be as follows. However, the present embodiment is not bound by the explanation of the reasons below.
[0014] In this embodiment, the iron alloy filler (A) containing the first filler (a1) and the second filler (a2) including iron alloy particles containing atoms of Fe, Si, B, and C and silicon oxide coating the surface of the iron alloy particles is adopted, and it is considered that even if the iron alloy filler (A) is filled, eddy current loss is unlikely to occur and the withstand voltage is unlikely to decrease. Therefore, it is considered that the magnetic permeability and insulating property can be maintained high in the cured product of the magnetic resin composition. In addition, the particles of the second filler (a2) having a small average particle size enter the gaps between the particles of the first filler (a1) having a large average particle size, thereby improving the filling property of the iron alloy filler (A), and it is considered that the fluidity can also be maintained well. Therefore, it is presumed that high magnetic permeability and insulating property can be realized without excessively increasing the filling rate of the iron alloy filler (A).
[0015] Thus, the magnetic resin composition of the present embodiment has high fluidity and therefore excellent moldability. In addition, the magnetic resin composition can be cured to form a cured product, and as described above, the cured product has high magnetic permeability and high insulating properties and is unlikely to cause eddy current loss, so it can be used well as a material for covering or sealing inductors, etc. For this reason, it can also be suitably used to produce electronic components such as magnetic elements that cover components such as inductors, and electronic devices equipped with the same.
[0016] 2.Details The magnetic resin composition according to this embodiment and the electronic component using the same will be described in detail below.
[0017] (1) Magnetic resin composition As already described, the magnetic resin composition of the present embodiment contains the iron alloy filler (A), the thermosetting resin (B), and the curing agent (C). Details of the components that can be contained in the magnetic resin composition will be described.
[0018] (iron alloy filler) The iron alloy filler (A) has electrical conductivity. The iron alloy filler (A) can be dispersed in the magnetic resin composition. The iron alloy filler (A) is a filler containing iron alloy particles containing iron (Fe) atoms as a main element. In the present disclosure, the main element refers to an element having the highest atomic ratio to the total number of atoms among the atomic species contained in the alloy particles. For example, Fe being the main element means that the ratio of Fe atoms to the total number of atoms contained in the iron alloy particles in the iron alloy filler (A) is 50 atm% or more. In the iron alloy particles, the ratio of Fe atoms to the total number of atoms is preferably 75 atm% or more and 95 atm% or less. If it is 75 atm% or more, it is easy to balance the crystalline components and amorphous components in the cured product of the magnetic resin composition, and it is easy to maintain high magnetic permeability. If it is 95 atm% or less, it is easy to further increase the magnetic permeability. In the iron alloy particles, the ratio of Fe atoms to the total number of atoms is more preferably 78 atm% or more, and even more preferably 81 atm% or more. In addition, in the iron alloy particles, the ratio of Fe atoms to the total number of atoms is more preferably 93 atm% or less, and even more preferably 90 atm% or less. Note that the iron alloy particles refer to iron-based alloys in particulate form. The alloy filler may be in the form of a powder.
[0019] The iron alloy filler (A) of this embodiment includes a first filler (a1) having an average particle size of 10 μm to 50 μm, and an iron alloy particle having an iron alloy particle containing all of the atoms of iron (Fe), silicon (Si), boron (B), and carbon (C), a silicon oxide coating the surface of the iron alloy particle, and a second filler (a2) having an average particle size of 1 μm to 5 μm. That is, the iron alloy filler (A) contains at least two fillers that are iron alloy particles whose surfaces are coated with silicon oxide and have different average particle size ranges. That is, the first filler (a1) and the second filler (a2) have at least different average particle size ranges. The average particle size of the first filler (a1) and the second filler (a2) is the average particle size of the particle group coated with silicon oxide. The method of coating the first filler (a1) and the second filler (a2) with silicon oxide in this embodiment will be described in detail later. The ratio of each element in the iron alloy filler (A) can be measured based on ICP (Inductively Coupled Plasma) mass spectrometry and calculated based on the results.
[0020] In this embodiment, the iron alloy filler (A) contains at least a first filler (a1) and a second filler (a2) having different average particle diameters. Specifically, the average particle diameter of the first filler (a1) is in the range of 10 μm to 50 μm, and the average particle diameter of the second filler (a2) is in the range of 1 μm to 5 μm. In this embodiment, the iron alloy filler (A) contains the first filler (a1) having a relatively large average particle diameter and the second filler (a2) having a small average particle diameter, which can contribute to improving the fluidity of the magnetic resin composition. Here, the average particle diameters of the first filler (a1) and the second filler (a2) refer to the median diameter D50 (50% particle diameter). The average particle diameters of the first filler (a1) and the second filler (a2) are obtained by measuring the particle size distribution by a laser diffraction / scattering method and calculating the volume-based particle diameter that is 50% of the integrated value obtained from the particle size distribution.
[0021] The average particle size of the first filler (a1) is preferably 20 μm or more, and more preferably 25 μm or more. The average particle size of the first filler (a1) is more preferably 40 μm or less, and more preferably 35 μm or less. If the average particle size is within this range, the loss in the cured product made from the magnetic resin composition can be reduced even when the cured product is used in the high frequency band, and in particular, the eddy current loss can be reduced.
[0022] The particle size of the second filler (a2) is preferably 1.0 μm or more, and more preferably 1.5 μm or more. The particle size of the second filler (a2) is more preferably 5.0 μm or less, and more preferably 4.5 μm or less. Within this range, even if the cured product made from the magnetic resin composition is used in a high frequency band, the loss in the cured product can be reduced, and in particular, the eddy current loss can be reduced.
[0023] The first filler (a1) preferably contains a crystalline component. In this case, the magnetic properties of the magnetic resin composition can be improved. In particular, in this case, the magnetic anisotropy of the magnetic resin composition can be reduced, and the core loss and magnetic permeability can be improved. In the present disclosure, crystalline means not being amorphous at room temperature (for example, 15 to 30°C). The crystalline component includes nanocrystals.
[0024] The compositions of the first filler (a1) and the second filler (a2) will be specifically described.
[0025] The iron alloy particles in the first filler (a1) contain Fe as the main element, and further contain Si, B, and C atoms as a composition. That is, the first filler (a1) contains Fe, Si, B, and C atoms. Therefore, it can contribute to improving the magnetic properties, particularly the magnetic permeability and the voltage resistance, of the cured product of the magnetic resin composition. The ratio of Fe atoms to all atoms of the iron alloy particles in the first filler (a1) is preferably 80 atm% or more and 95 atm% or less. If it is 80 atm% or more, it is easy to balance the crystalline components and the amorphous components in the cured product of the magnetic resin composition, and it is easier to maintain a high magnetic permeability. If it is 95 atm% or less, it is easy to further increase the magnetic permeability. It is more preferable that the ratio of Fe atoms to all atoms of the iron alloy particles in the first filler (a1) is 90 atm% or less. In the present disclosure, the iron alloy particles in the first filler (a1) may contain oxygen atoms. The inclusion of oxygen atoms includes the oxidization of Fe, Si, B, or C atoms contained in the iron alloy particles.
[0026] The ratio of Si atoms to all atoms of the iron alloy particles in the first filler (a1) is preferably 2 atm% or more and 10 atm% or less. The ratio of B atoms to all atoms of the iron alloy particles in the first filler (a1) is preferably 1 atm% or more and 5 atm% or less. The ratio of C atoms to all atoms of the iron alloy particles in the first filler (a1) is preferably 0.01 atm% or more and 1.0 atm% or less. In the present disclosure, the ratio of Si atoms to all atoms of the iron alloy particles in the first filler (a1) refers to the ratio in the iron alloy particles before being coated with silicon oxide.
[0027] The iron alloy particles in the first filler (a1) preferably further contain at least one atom selected from the group consisting of niobium (Nb), copper (Cu), and chromium (Cr). In this case, the high fluidity of the magnetic resin composition can be maintained, and the magnetic permeability of the cured product of the magnetic resin composition is more likely to be increased. The ratio of Nb atoms to all atoms of the iron alloy particles in the first filler (a1) is preferably 1 atm% or more and 10 atm% or less. The ratio of Cu atoms to all atoms of the iron alloy particles in the first filler (a1) is preferably 0.1 atm% or more and 5.0 atm% or less. The ratio of Cr atoms to all atoms of the iron alloy particles in the first filler (a1) is preferably 0.01 atm% or more and 0.3 atm% or less. The iron alloy particles in the first filler (a1) may contain atoms other than the above, as long as it does not excessively deviate from the purpose of the present disclosure.
[0028] The iron alloy particles in the second filler (a2) have a composition in which Fe is the main atom, and further contains Si, B, and C atoms, similar to the first filler (a1). That is, the second filler (a2) contains Fe, Si, B, and C atoms. This can contribute to improving the magnetic properties, particularly the magnetic permeability and the voltage resistance, of the cured product of the magnetic resin composition. The ratio of Fe atoms in the iron alloy particles in the second filler (a2) is the remainder excluding atoms other than Fe that may be contained in the iron alloy particles. In the present disclosure, the iron alloy particles in the second filler (a2) may contain oxygen atoms. The inclusion of oxygen atoms includes the oxidation of Fe, Si, B, or C atoms contained in the iron alloy particles.
[0029] The ratio of Si atoms to all atoms of the iron alloy particles in the second filler (a2) is preferably 1 atm% or more and 10 atm% or less. The ratio of B atoms to all atoms of the iron alloy particles in the second filler (a2) is preferably 1 atm% or more and 5 atm% or less. The ratio of C atoms to all atoms of the second filler (a2) is preferably 0.1 atm% or more and 2.0 atm% or less. The iron alloy particles in the second filler (a2) may contain atoms other than those mentioned above, as long as it does not excessively deviate from the purpose of the present disclosure.
[0030] The manufacturing method of the first filler (a1) and the second filler (a2) of this embodiment will be described with reference to an example, however, the manufacturing method of the first filler (a1) and the second filler (a2) is not limited to the following method.
[0031] In order to prepare the first filler (a1) and the second filler (a2), a method capable of coating suitable particles, such as a gas phase method or a liquid phase method, can be adopted.
[0032] First, an alloy material as the raw material of the first filler (a1) is prepared, and the alloy material is pulverized to an appropriate size and shape to prepare iron alloy particles. The alloy material is preferably an alloy containing atoms of Fe, Si, B, and C. The pulverization method may be, for example, mechanical pulverization, molten metal pulverization, physical pulverization, or chemical pulverization. Examples of mechanical pulverization include the stamp mill method, the ball mill method, and the hammer mill method. Examples of molten metal pulverization include the high-pressure water spray method (water atomization method), the ultra-high-pressure water spray method, the gas atomization method (gas atomization method), the rotating electrode method, and the vacuum spray method. Examples of physical or chemical pulverization include the electrolysis method, the gas reduction method, the solid reduction method, the carbonyl method, the hydride decomposition method, the evaporation condensation method, and the amalgam method.
[0033] In the liquid phase method, for example, iron alloy particles are mixed into water or a mixture of water and an organic solvent to disperse the iron alloy particles. The surfaces of the iron alloy particles may be coated with a thermosetting material, or an oxide film may be formed by a dehydration reaction of a metal alkoxide such as tetraethyloxysilane or tetramethyloxysilane. In this case, the surfaces of the iron alloy particles are more easily coated in the sol-gel reaction described below.
[0034] Then, a silane coupling agent is added as a coupling agent to the mixture, and the mixture is mixed and stirred. Then, silicon oxide can be formed on the surface of the iron alloy particles by a sol-gel reaction. The silane coupling agent can be at least one selected from the group consisting of trimethoxysilane, tetramethoxysilane, triethoxysilane, tetraethoxysilane, tripropoxysilane, tetrapropoxysilane, tributoxysilane, and tributoxysilane.
[0035] As a result, the first filler (a1) made of iron alloy particles having the surface coated with silicon oxide is obtained.
[0036] In the gas phase method, for example, the alloy material as the raw material of the first filler (a1) and the coupling agent are prepared, and the alloy material is placed at the top of a container, and the coupling agent is placed below it. The coupling agent may be a compound similar to the silane coupling agent described above.
[0037] The container is then sealed and heated to volatilize the coupling agent. This allows the coupling agent to adhere to the surface of the alloy material, resulting in a coated alloy material in which silicon oxide is formed on the surface of the alloy material. The gas phase method may be performed under atmospheric pressure or under vacuum.
[0038] The coated alloy material is crushed by an appropriate method as described above, and then separated into iron alloy particles coated with silicon oxide and iron alloy particles not coated with silicon oxide. This results in a first filler (a1) made of iron alloy particles coated with silicon oxide. In the gas phase method, the coated alloy material is prepared and then crushed into particles to prepare the first filler (a1). However, the alloy material may be crushed in advance to prepare iron alloy particles, and a coupling agent may be attached to the iron alloy particles to prepare the first filler (a1). In addition, the surface of the raw iron alloy particles may be coated with a thermosetting material, or an oxide film may be formed by a dehydration reaction of a metal alkoxide such as tetraethyloxysilane or tetramethyloxysilane, as in the liquid phase method.
[0039] The second filler (a2) is similar to the above, except that the average particle diameter is adjusted.
[0040] The thickness of the silicon oxide coating the surface of the iron alloy particles in the first filler (a1) is preferably 1 nm or more and 100 nm or less. In this case, high fluidity can be maintained, high magnetic permeability of the cured product can be maintained, and the insulating properties of the cured product can be easily improved. The thickness of the silicon oxide coating the surface of the iron alloy particles in the first filler (a1) is more preferably 5 nm or more. In addition, the thickness of the silicon oxide coating the surface of the iron alloy particles in the first filler (a1) is more preferably 50 nm or less, and even more preferably 40 nm or less.
[0041] The thickness of the silicon oxide coating the surface of the iron alloy particles in the second filler (a2) is preferably 1 nm or more and 50 nm or less. In this case, high fluidity can be maintained, high magnetic permeability of the cured product can be maintained, and the insulating properties of the cured product can be easily improved. The thickness of the silicon oxide coating the surface of the iron alloy particles in the second filler (a2) is more preferably 3 nm or more. Moreover, the thickness of the silicon oxide coating the surface of the iron alloy particles in the second filler (a2) is more preferably 30 nm or less, and even more preferably 10 nm or less.
[0042] In the present disclosure, the thickness of the silicon oxide in the first filler (a1) and the second filler (a2) can be confirmed from an SEM image obtained by observing the surface with a scanning electron microscope.
[0043] The content of the iron alloy filler (A) relative to the total solid content of the magnetic resin composition is preferably 85% by mass or more and 97% by mass or less. If it is 85% by mass or more, the magnetic resin composition can contain a large amount of crystalline components. This makes it more difficult for the iron alloy filler (A) to aggregate in the magnetic resin composition, and makes it easier to improve the magnetic permeability of the cured product of the magnetic resin composition. If it is 97% by mass or less, the magnetic resin composition can contain components other than the iron alloy filler (A), making it easier to adjust the magnetic properties well. In the present disclosure, the total solid content of the magnetic resin composition refers to the total amount of components excluding volatile components, such as solvents, among the components that can be contained in the magnetic resin composition.
[0044] The mass ratio of the first filler (a1) to the second filler (a2) in the iron alloy filler (A) is preferably within the range of 85:15 to 65:35. The iron alloy filler (A) may contain an iron-based alloy filler other than the first filler (a1) and the second filler (a2) described above, as long as it does not excessively deviate from the effects of the present disclosure. When the iron alloy filler (A) contains an iron-based alloy filler other than the first filler (a1) and the second filler (a2), the total ratio of the first filler (a1) and the second filler (a2) to the iron alloy filler (A) is preferably 60 mass% or more, more preferably 80 mass% or more.
[0045] (thermosetting resin) The thermosetting resin (B) functions as a so-called binder in the cured product of the magnetic resin composition. That is, the thermosetting resin (B) has a function of being interposed between particles of the iron alloy filler (A) in the cured product of the magnetic resin composition and binding them together. Note that binding does not mean that all particles of the iron alloy filler (A) are directly bonded together.
[0046] The thermosetting resin (B) can have electrical insulation properties, and therefore when the magnetic resin composition is cured, the thermosetting resin (B) can penetrate to fill the gaps between the particles of the iron alloy filler (A), thereby improving the electrical insulation properties of the cured product of the magnetic resin composition. In addition, the thermosetting resin (B) can improve the moldability when molding the composite magnetic material to produce a cured product.
[0047] Examples of the thermosetting resin (B) include, but are not limited to, epoxy resin, phenol resin, phenoxy resin, silicon resin, polyimide, and organic phosphoric acid compound. The thermosetting resin (B) preferably contains an epoxy resin. In this case, the fluidity of the magnetic resin composition is easily increased, and the curability can be further improved. Examples of the epoxy resin include alkylphenol novolac type epoxy resins such as phenol novolac type epoxy resins and cresol novolac type epoxy resins; naphthol novolac type epoxy resins; phenol aralkyl type epoxy resins having a phenylene skeleton, a biphenylene skeleton, or the like; biphenyl aralkyl type epoxy resins; naphthol aralkyl type epoxy resins having a phenylene skeleton, a biphenylene skeleton, or the like; polyfunctional epoxy resins such as triphenol methane type epoxy resins and alkyl modified triphenol methane type epoxy resins; triphenyl methane type epoxy resins; tetrakisphenol ethane type epoxy resins; dicyclopentadiene type epoxy resins; and one or more components selected from the group consisting of ene-type epoxy resins; stilbene-type epoxy resins; bisphenol-type epoxy resins such as bisphenol A-type epoxy resins and bisphenol F-type epoxy resins; biphenyl-type epoxy resins; naphthalene-type epoxy resins; alicyclic epoxy resins; bromine-containing epoxy resins such as bisphenol A-type bromine-containing epoxy resins; glycidylamine-type epoxy resins obtained by reacting polyamines such as diaminodiphenylmethane or isocyanuric acid with epichlorohydrin; and glycidyl ester-type epoxy resins obtained by reacting polybasic acids such as phthalic acid or dimer acid with epichlorohydrin.
[0048] The thermosetting resin (B) may be, for example, in a liquid state or in a solid state.
[0049] The magnetic resin composition may contain a curable component other than the thermosetting resin (B) For example, the magnetic resin composition may contain a photocurable component.
[0050] The proportion of the thermosetting resin (B) relative to the total solid content of the magnetic resin composition is preferably, for example, from 1 mass % to 10 mass %.
[0051] (hardening agent) The curing agent (C) can have a function of curing the curable component in the magnetic resin composition. In this embodiment, the curing agent (C) can cure the thermosetting resin (B) in the magnetic resin composition. In addition, the curing agent (C) can improve the physical properties of the cured product of the magnetic resin composition.
[0052] Specific examples of the curing agent (C) include phenol-based curing agents, acid anhydride-based curing agents, aliphatic amine-based curing agents, and aromatic amine-based curing agents. When the magnetic resin composition contains an epoxy resin, the curing agent (C) preferably contains a phenol-based curing agent. In this case, the flowability of the magnetic resin composition is further increased, and the curability can be further improved. Examples of the phenol-based curing agent include phenol novolac resin, cresol novolac resin, biphenyl novolac resin, triphenylmethane resin, naphthol novolac resin, phenol aralkyl resin, and biphenyl aralkyl resin.
[0053] The proportion of the curing agent (C) relative to the total amount of the thermosetting resin (B) is preferably 30% by mass or more and 50% by mass or less.
[0054] (Other Ingredients) The magnetic resin composition may contain other appropriate components (hereinafter referred to as "other components") other than those described above, as long as they do not deviate from the purpose of the present disclosure. For example, the magnetic resin composition may contain other components such as a curing accelerator, a release agent, a modifier, and a filler.
[0055] The curing accelerator can further improve the curing property of the magnetic resin composition. Examples of the curing accelerator include organic phosphines such as triphenylphosphine, tributylphosphine, and tetraphenylphosphonium tetraphenylborate, tertiary amines such as 1,8-diaza-bicyclo(5,4,0)undecene-7 (DBU), triethylenediamine, and benzyldimethylamine, and imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, and 2-phenyl-4-methylimidazole. In the present disclosure, the curing accelerator may also include components belonging to a curing catalyst and a curing assistant.
[0056] The release agent can improve the releasability when the magnetic resin composition is molded and removed from a mold, etc. Examples of the release agent include carnauba wax, stearic acid, montanic acid, carboxyl group-containing polyolefin, ester wax, polyethylene oxide, and metal soap.
[0057] The modifier or lubricant can improve the dispersibility of the components in the magnetic resin composition or modify the surface. Examples of the modifier include coupling agents and surfactants. Examples of the coupling agent include at least one component selected from the group consisting of silane coupling agents, titanium-based coupling agents, titanium alkoxides, and titanium chelates. Examples of the surfactant include ionic surfactants and nonionic surfactants.
[0058] The filler can improve the physical properties of the cured product of the magnetic resin composition. Examples of the filler include inorganic fillers and organic fillers. The inorganic filler includes at least one selected from the group consisting of, for example, spherical silica, fused silica, talc (hydrated magnesium silicate), alumina (aluminum oxide), magnesium oxide, titanium oxide, zirconium oxide, and mica. However, in the present disclosure, the inorganic filler does not include the components contained in the iron alloy filler (A).
[0059] (2) Preparation of magnetic resin composition and production of cured product The magnetic resin composition of the present embodiment can be prepared, for example, as follows.
[0060] First, the above-mentioned first filler (a1) and second filler (a2) as the iron alloy filler (A), the thermosetting resin (B), the curing agent (C), and appropriate components (e.g., other components) as required are prepared.
[0061] Then, for example, the iron alloy filler (A), the hardener (C), and other appropriate components, if necessary, are placed in a container, mixed, and dispersed uniformly.
[0062] Next, the thermosetting resin (B) is added, and if necessary, additives, a solvent, etc. are added, and the mixture is kneaded. When adding the thermosetting resin (B), the thermosetting resin (B) may be added in a state where it is dissolved in a solvent in advance to the mixture of the iron alloy filler (A) and the curing agent (C). In addition, a suitable kneading device can be used for kneading. The conditions for kneading may be appropriately adjusted depending on the type of thermosetting resin, the melting start temperature, etc., and for example, the heating temperature can be set to a temperature lower than the temperature at which the thermosetting resin starts to harden. In this way, a magnetic resin composition can be prepared.
[0063] The kneaded magnetic resin composition may be heated at an appropriate temperature to dry the magnetic resin composition. When a solvent such as an organic solvent is added during kneading, it is preferable to heat and dry the composition at a temperature at which the solvent can volatilize. The dried magnetic resin composition may be pulverized by an appropriate pulverizing device or the like to obtain a powdered magnetic resin composition. For pulverization, a stamp mill method, a ball mill method, a hammer mill method, or the like may be used. The magnetic resin composition may be pulverized and then pelletized. In this way, the shape or properties of the magnetic resin composition are not particularly limited.
[0064] To harden the magnetic resin composition, the magnetic resin composition is heated to harden the thermosetting resin (B). This results in a hardened magnetic resin composition. Conditions such as heating temperature and heating time may be appropriately adjusted depending on the type of thermosetting resin (B) and the type and combination of curing agent (C), but the heating temperature is, for example, 150°C or higher and 300°C or lower, and the heating time is 1 minute or higher and 10 hours or lower. The method for hardening the magnetic resin composition is not limited to the above.
[0065] (Physical properties and characteristics of magnetic resin composition and cured product) The spiral flow length of the magnetic resin composition measured based on ASTM 3123 is preferably 60 cm or more. In this case, the magnetic resin composition has high fluidity. The spiral flow length is more preferably 70 cm or more, and even more preferably 90 cm or more. The upper limit of the spiral flow length is not particularly limited, but is 200 cm or less. The spiral flow length of the magnetic resin composition in the present disclosure can be measured based on the method and conditions described in "(3-1) Spiral Flow (SF)" in the Examples below.
[0066] The magnetic permeability of the cured product of the magnetic resin composition is preferably 20 or more. In this case, the cured product of the magnetic resin composition has high magnetic properties. The magnetic permeability is more preferably 22 or more, and even more preferably 23 or more. The upper limit of the magnetic permeability of the magnetic resin composition is not particularly limited, but is 40 or less. The magnetic permeability of the cured product of the magnetic resin composition of the present disclosure can be measured and calculated based on the method and conditions described in "(3-2) Magnetic permeability" in the examples below.
[0067] The withstand voltage of the cured product of the magnetic resin composition is preferably 400 V / mm or more. In this case, the cured product of the magnetic resin composition can have high insulating properties. The withstand voltage of the cured product of the magnetic resin composition is more preferably 700 V / mm or more, and even more preferably 1000 V / mm or more. There is no particular upper limit to the withstand voltage of the cured product of the magnetic resin composition. The withstand voltage of the cured product of the magnetic resin composition in this disclosure can be measured and calculated based on the method described in "(3-3) Withstand voltage" in the examples below.
[0068] As described above, the magnetic resin composition of this embodiment has high fluidity and excellent moldability, and can simultaneously improve the magnetic permeability and voltage resistance of the cured product. Therefore, the magnetic resin composition of this embodiment can be suitably used to manufacture electronic components by molding into a desired shape and curing. For example, to manufacture an electronic component 100 including a passive element 1 such as an inductor and an inductor component and a sealing part 2 that seals the passive element 1, the magnetic resin composition of this embodiment can be used for the sealing part 2. That is, the electronic component 100 includes a passive element 1 and a sealing part 2 that seals the passive element 1, and the sealing part 2 includes a cured product of the magnetic resin composition.
[0069] (3) Electronic Components An example of an electronic component using the magnetic resin composition of the present embodiment will be described with reference to the drawings (FIGS. 1 to 3). Note that each drawing is a schematic drawing, and the size and thickness ratios of each component in each drawing do not necessarily reflect the actual dimensional ratios.
[0070] The electronic component 100 according to the present embodiment may be an electronic device itself that functions as a device, or may be an inductor or a component having an inductor function that is used in an electronic device. The electronic component 100 may also be a package component 101 that includes a passive element 1 and a package (exterior 3) that includes a sealing portion 2 that seals the passive element 1.
[0071] 1 shows an electronic component 100 which is a packaging component 101. The electronic component 100 (packaging component 101) includes a passive element 1 and a sealing portion 2. The sealing portion 2 seals the passive element 1. Furthermore, the sealing portion 2 contains a cured product of the magnetic resin composition described above.
[0072] The passive element 1 is an element that releases, stores, or consumes supplied power. In this embodiment, the passive element 1 is, for example, an inductor or a component having an inductor function. The passive element 1 has a coil conductor portion 11.
[0073] The coil conductor 11 is formed by winding a copper wire so as to have an air core. The coil conductor 11 may be, for example, a round wire coil formed by winding a round copper wire, or an edgewise coil formed by winding a rectangular copper wire. The type and shape of the coil conductor 11 are not limited to those described above.
[0074] The passive element 1 may include a core 13 that passes through the hollow core portion of the coil conductor portion 11. The core 13 may be, for example, a ferrite core, but is not limited to this.
[0075] The electronic component 100 may include a pair of connection terminals 4. The connection terminals 4 are connected to both ends 12 of the coil conductor portion 11, respectively. The connection terminals 4 may be connected to an external electrode or the like. Therefore, by connecting the connection terminals 4 to the external electrodes, a current can be passed through the coil conductor portion 11.
[0076] The sealing part 2 seals the passive element 1 in the electronic component 100 (package part 101). In the present disclosure, "sealing" also includes covering the object to be sealed (passive element 1 in FIG. 1). Therefore, it can be said that the passive element 1 is covered with a cured product of the magnetic resin composition. The sealing part 2 may constitute the exterior 3 of the electronic component 100. That is, the sealing part 2 can seal the passive element 1 with a cured product of the magnetic resin composition, but the cured product of the magnetic resin composition can also constitute the exterior 3 of the electronic component 100. More specifically, in FIG. 1, the passive element 1 mounted on the substrate 9 is sealed with a cured product of the magnetic resin composition, while the cured product of the magnetic resin composition also serves as the peripheral surface part 31 and the bottom surface part 32 of the exterior 3.
[0077] The package component 101 shown in FIG. 1 can be produced, for example, as follows.
[0078] That is, as shown in FIG. 2A, a passive element 1 having a coil conductor portion 11 is placed in a cavity 63 of a mold 6 having a lower mold 61 and an upper mold 62. In FIG. 2A, the passive element 1 is placed in the cavity 63 with the tip 12 of the coil conductor portion 11 connected to the connection terminal 4. Then, a magnetic resin composition is injected from an injection port 64 of the mold 6 (see FIG. 2B). As a result, the passive element 1 is covered with the magnetic resin composition. If necessary, the magnetic resin composition is heated and cured, whereby an electronic component 100 (package component 101) including the passive element 1 and a sealing portion 2 can be produced.
[0079] Here, when the core 13 is not present in the hollow core portion of the coil conductor portion 11, the hollow core portion may be filled with a magnetic resin composition and the magnetic resin composition may be cured to produce the core 13. In other words, the cured product of the magnetic resin composition may serve as both the sealing portion 2 and the core 13. Therefore, the magnetic resin composition may constitute not only the sealing portion 2 and the exterior 3 but also the core 13. As described above, the magnetic resin composition of this embodiment may improve the magnetic permeability and voltage resistance of the cured product, and therefore, when the core 13 is produced from the magnetic resin composition, an electronic component 100 with improved performance or reduced size may be produced.
[0080] In the above, the magnetic resin composition is described as sealing an inductor or inductor component, which is a passive element 1, in a cavity, i.e., filling the cavity for producing the electronic component 100 with the magnetic resin composition in a state in which the passive element 1 is placed, but the method of using the magnetic resin composition is not limited to the above. For example, the exterior 3 that covers the passive element 1 that is not placed in the cavity may be produced from the magnetic resin composition.
[0081] 3 shows a case where the passive element 1 is a reactor 110. The reactor 110 shown in FIG. 3 has a first coil conductor portion 111 and a second coil conductor portion 112 as the coil conductor portion 11. The first coil conductor portion 111 and the second coil conductor portion 112 each have a tip portion (not shown) connected to a corresponding pair of connection terminals 4 (first connection terminal 41, second connection terminal 42). The reactor 110 also has a core 13 that passes through the air-core portions of the first coil conductor portion 111 and the second coil conductor portion 112. The core 13 extends beyond the first coil conductor portion 111 and the second coil conductor portion 112 in the winding axis direction and is connected in a direction perpendicular to the winding axis direction.
[0082] 3, the passive element 1 is also encapsulated with the cured product of the magnetic resin composition 2. Specifically, the cured product of the magnetic resin composition covers and encapsulates the coil conductor portion 11 and the core 13 of the passive element 1.
[0083] (Modification) The magnetic resin composition can also be used, for example, to make a dust core.
[0084] Furthermore, examples of the inductor component that is the passive element 1 in the electronic component 100 include, in addition to a coil, an inductor, a reactor having an inductor function, and a transformer.
[0085] Further, a suitable base material used in a semiconductor device may be adopted as the substrate 9. Examples of the base material in the substrate 9 include insulating substrates made of glass epoxy, polyimide, polyester, ceramic, etc. The substrate 9 may include conductive wiring made of a conductor such as copper formed on the surface of the base material.
[0086] (4) Summary As is apparent from the above-described embodiments, the present disclosure includes the following aspects. In the following, reference symbols are given in parentheses only to clarify the correspondence with the embodiments.
[0087] The magnetic resin composition according to the first embodiment contains an iron alloy filler (A), a thermosetting resin (B), and a curing agent (C). The iron alloy filler (A) contains a first filler (a1) having an average particle size of 10 μm to 50 μm, the first filler (a1) including iron alloy particles containing all of the atoms of iron, silicon, boron, and carbon, and a silicon oxide coating the surface of the iron alloy particles, and a second filler (a2) having an average particle size of 1 μm to 5 μm, the second filler (a2) including iron alloy particles containing all of the atoms of iron, silicon, boron, and carbon, and a silicon oxide coating the surface of the iron alloy particles.
[0088] According to this embodiment, the fluidity can be increased, and the cured product can have high magnetic permeability and high insulating properties.
[0089] In the magnetic resin composition according to the second embodiment, in the first embodiment, the ratio of Fe atoms to the total number of atoms in the iron alloy particles in the first filler (a1) is 75 atm % or more and 95 atm % or less.
[0090] According to this embodiment, high fluidity can be maintained, and the magnetic permeability of the cured product can be easily further increased.
[0091] In the magnetic resin composition according to the third aspect, in the first or second aspect, the iron alloy particles in the first filler (a1) further contain at least one atom selected from the group consisting of niobium, copper, and chromium.
[0092] According to this embodiment, high fluidity can be maintained, and the magnetic permeability of the cured product can be easily further increased.
[0093] A magnetic resin composition according to a fourth aspect is any one of the first to third aspects, in which the iron alloy particles in the first filler (a1) contain a crystalline component.
[0094] According to this embodiment, the magnetic properties of the cured product of the magnetic resin composition can be improved, and therefore the magnetic permeability and insulating properties of the cured product can be further improved.
[0095] The magnetic resin composition according to the fifth aspect is any one of the first to fourth aspects, in which the thickness of the silicon oxide coating the surface of the iron alloy particle in the first filler (a1) is 1 nm or more and 100 nm or less.
[0096] According to this embodiment, high fluidity can be maintained, high magnetic permeability of the cured product can be maintained, and the insulating properties of the cured product can be more easily improved.
[0097] A magnetic resin composition according to a sixth aspect is any one of the first to fifth aspects, wherein the thermosetting resin (B) contains an epoxy resin, and the curing agent (C) contains a phenol-based curing agent.
[0098] According to this embodiment, it is easy to improve the fluidity and the hardening property.
[0099] The magnetic resin composition according to the seventh aspect is any one of the first to sixth aspects, in which the content of the iron alloy filler (A) relative to the total solid content of the magnetic resin composition is 85 mass% or more and 97 mass% or less.
[0100] The magnetic resin composition according to the eighth aspect is used in any one of the first to seventh aspects to produce a sealing portion (2) in an electronic component (100) having a passive element (1) and a sealing portion (2) that seals the passive element (1).
[0101] According to the eighth aspect, an electronic component (100) having excellent moldability, high magnetic permeability and insulating properties can be obtained.
[0102] According to this embodiment, high fluidity can be maintained, and the magnetic permeability of the cured product can be easily further increased.
[0103] An electronic component (100) according to a ninth aspect includes a passive element (1) and a sealing part (2) that seals the passive element (1). The sealing part (2) includes a cured product of the magnetic resin composition according to any one of the first to seventh aspects.
[0104] According to the ninth aspect, an electronic component (100) having excellent moldability, high magnetic permeability and insulating properties can be obtained. EXAMPLES
[0105] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to the following examples.
[0106] (1) Preparation of iron alloy filler Using magnetic powders 1 to 4, which are "magnetic particles" shown below, as raw materials, iron alloy fillers 1 to 10, which are "magnetic materials" shown in Table 1 and shown below, were prepared.
[0107] Specifically, for the iron alloy filler 2, the magnetic powder 1 was mixed and dispersed in a mixture of water and an organic solvent, and then a silane compound (TEOS: tetraethoxysilane) was added and mixed to cause a sol-gel reaction, thereby obtaining the iron alloy filler 2 in which the surfaces of the magnetic particles 1 were coated with the silane compound to a thickness of 10 nm.
[0108] Iron alloy filler 3 was prepared in the same manner as above-mentioned iron alloy filler 2, except that the film thickness was changed to 10 μm.
[0109] The iron alloy filler 4 was prepared by blending and dispersing the magnetic powder 1 in a mixture of water and an organic solvent, then adding and mixing the phosphorus compound to cause a sol-gel reaction. This resulted in the iron alloy filler 4 having the surfaces of the magnetic particles 1 coated with the phosphorus compound to a thickness of 10 nm.
[0110] Iron alloy filler 5 was prepared in the same manner as above-mentioned iron alloy filler 2, except that the magnetic powder was changed to magnetic powder 2.
[0111] Iron alloy filler 6 was prepared in the same manner as above-mentioned iron alloy filler 3, except that magnetic powder 2 was changed to magnetic powder 2.
[0112] Iron alloy filler 7 was prepared in the same manner as above-mentioned iron alloy filler 2, except that the magnetic powder was changed to magnetic powder 3.
[0113] Iron alloy filler 9 was prepared in the same manner as above-mentioned iron alloy filler 2, except that the magnetic powder was changed to magnetic powder 4.
[0114] The iron alloy filler 10 was prepared in the same manner as the iron alloy filler 3, except that the magnetic powder was changed to the magnetic powder 4.
[0115] The iron alloy filler 1 is the same as the magnetic powder 1, and the iron alloy filler 8 is the same as the magnetic powder 4.
[0116] (magnetic particles) Magnetic powder 1: Epson Atmix Corporation product name: KUAMET NCI (iron alloy particles containing Fe, Si, B, C, Nb, Cu, and Cr (Si: 7.7 atm%, B: 2.0 atm%, C: 0.035 atm%, Nb: 5.7 atm%, Cu: 1.3 atm%, Cr: 0.05 atm%, Fe: balance (83.2 atm%). Average particle size (D50): 28 μm. Crystalline.)).
[0117] Magnetic powder 2: Epson Atmix Corporation, product name KUAMET 9A4 (iron alloy particles containing Fe, Si, B, and C (Si: 3.4 atm%, B: 3.1 atm%, C: 0.50 atm%, Fe: balance (92.7 atm%). Average particle size (D50): 25 μm. Amorphous).)
[0118] Magnetic powder 3: Sanyo Special Steel Co., Ltd. Product name PST-SHT (iron alloy particles containing Fe, Si, and Al (Si: 5-10atm%, Al: 5-10atm%, Fe: balance (80-90atm%), average particle size (D50): 29μm. Crystalline. Non-spherical.)).
[0119] Magnetic powder 4: Epson Atmix Corporation, product name AW2-08 PF-3K (iron alloy particles containing Fe, Si, B, C, Nb, Cu, Cr, Mn, P, and S (Si: 7.7 atm%, B: 2.0 atm%, C: 0.035 atm%, Nb: 5.7 atm%, Cu: 1.3 atm%, Cr: 0.05 atm%, Mn: 0.35 atm%, P: 0.02 atm%, S: 0.0075 atm%, Fe: balance (87.2 atm%), average particle size (D50): 3.2 μm. Amorphous).)
[0120] (2) Preparation of magnetic resin composition In each of the examples and comparative examples, the components shown in the table, except for the "curing agent" and "magnetic material", were mixed in the mixing ratio (parts by mass) shown in the table to prepare a mixed liquid. Next, the "magnetic material" was added to the mixed liquid and kneaded, and finally the "curing agent" was added and stirred until uniform. This resulted in a magnetic resin composition. Details of the components shown in the table are as follows. (thermosetting resin) Epoxy resin 1: Biphenyl type epoxy resin (product name YX-4000H, manufactured by Mitsubishi Chemical Corporation). Epoxy resin 2: Phenol aralkyl type epoxy resin (product name NC-3000-L, manufactured by Nippon Kayaku Co., Ltd.). (hardening agent) Phenol hardener 1: Aralkyl phenolic resin (UBE Corporation product name MEHC-7851SS). Phenolic hardener 2: Novolac type phenolic resin (UBE Corporation product name DL-92). Phenolic hardener 3: Aralkyl phenolic resin (UBE Corporation product name MEHC-7841-4S). (Cure accelerator) Curing accelerator 1: A 1:4 reaction product of TPP-K manufactured by Hokko Chemical Industry Co., Ltd. and H-4 manufactured by UBE Corporation. Curing accelerator 2: Imidazole-based curing agent (manufactured by Shikoku Chemical Industry Co., Ltd., product name 2P4MHZ-PW). Curing accelerator 3: Imidazole-based curing agent (product name 2PHZ-PW, manufactured by Shikoku Chemical Industry Co., Ltd.). (Others: additives, etc.) Silane coupling agent 1: Aminosilane coupling agent (product name KBM-573, manufactured by Shin-Etsu Chemical Co., Ltd.). Silane coupling agent 2: Mercaptosilane coupling agent (product name KBM-802, manufactured by Shin-Etsu Chemical Co., Ltd.). Additive 1: A 1:4 reaction product of XF42-A0454 manufactured by Momentive and H-1M manufactured by UBE Corporation. Release agent: Product name WAXMB87 manufactured by Dainichi Chemical Industry Co., Ltd. Filler: Spherical silica (product name SFP-10MK, manufactured by Denka Co., Ltd.).
[0121] (3) Evaluation (3-1) Spiral Flow (SF) The magnetic resin composition was subjected to injection molding in accordance with ASTM 3123 using a spiral flow mold at a mold temperature of 175°C and an injection pressure of 6.86MPa (70kgf / cm 2 The magnetic resin composition was molded under the conditions of 100 cm to 180 cm for a molding time of 180 seconds, and the distance it flowed (flow distance) in 180 seconds from the start of molding was measured. The values obtained by the measurement are shown in Table 1. If the flow distance is 70 cm or more, it can be determined that the fluidity when molten is excellent.
[0122] (3-2) Magnetic permeability The magnetic resin composition prepared in (2) was made into a paste and then pulverized to obtain a powdered magnetic resin composition. The powdered magnetic resin composition was molded into a toroidal shape having dimensions of an outer diameter of φ7 mm, an inner diameter of φ3 mm, and a thickness of about 1 mm, and cured in a thermostatic chamber at 175°C for 6 hours to produce a test piece of the cured product. The real part of the complex relative permeability at 2 MHz was determined for this test piece using an impedance analyzer (manufactured by Keysight Corporation, model number E4991B). The values are shown in Table 1.
[0123] (3-3) Voltage resistance The magnetic resin composition prepared in (2) was made into a paste and then pulverized to obtain a powdered magnetic resin composition. The powdered magnetic resin composition was molded into a disk shape having an outer diameter of φ60 mm and a thickness of about 0.7 mm, and cured in a thermostatic chamber at 175°C for 6 hours to prepare a test piece of the cured product. The voltage of this test piece was increased stepwise with an insulation resistance measuring device (models R8340A and TR42) manufactured by ADVANTEST Co., Ltd., with a sweep start voltage of 10 V and a sweep interval of 10 V. The applied voltage was measured and recorded when a limit current of 5 mA flowed. The results are shown in Table 1.
[0124] [Table 1] [Explanation of symbols]
[0125] 1 Passive elements 2 Sealing part 100 Electronic Components
Claims
1. Iron alloy filler (A) A thermosetting resin (B); A curing agent (C), The iron alloy filler (A) is A first filler (a1) comprising iron alloy particles containing atoms of iron, silicon, boron, and carbon, and a silicon oxide coating the surfaces of the iron alloy particles, and having an average particle size of 10 μm or more and 50 μm or less; The second filler (a2) comprises iron alloy particles containing atoms of iron, silicon, boron, and carbon, and a silicon oxide coating the surfaces of the iron alloy particles, and has an average particle size of 1 μm or more and 5 μm or less. Magnetic resin composition.
2. The ratio of Fe atoms to the total number of atoms of the iron alloy particles in the first filler (a1) is 75 atm% or more and 95 atm% or less. The magnetic resin composition according to claim 1 .
3. The iron alloy particles in the first filler (a1) further contain at least one atom selected from the group consisting of niobium, copper, and chromium. The magnetic resin composition according to claim 1 .
4. The iron alloy particles in the first filler (a1) contain a crystalline component, The magnetic resin composition according to claim 1 .
5. The thickness of the silicon oxide coating the surface of the iron alloy particle in the first filler (a1) is 1 nm or more and 100 nm or less. The magnetic resin composition according to claim 1 .
6. The thermosetting resin (B) contains an epoxy resin, The curing agent (C) contains a phenol-based curing agent. The magnetic resin composition according to claim 1 .
7. The content of the iron alloy filler (A) relative to the total solid content of the magnetic resin composition is 85% by mass or more and 97% by mass or less. The magnetic resin composition according to claim 1 .
8. In an electronic component including a passive element and a sealing portion that seals the passive element, a method for manufacturing the sealing portion is provided. The magnetic resin composition according to claim 1 .
9. a passive element; and a sealing portion that seals the passive element, The sealing portion includes a cured product of the magnetic resin composition according to any one of claims 1 to 7. Electronic components.
Citation Information
Patent Citations
Electronic circuit package arranged by using composite magnetic sealing material
JP2019135770A